Pengaruh Konsumsi Air Kelapa Muda terhadap Peningkatan Kadar Hemoglobin pada Ibu Post Partum - Ali, Rizky Nikmathul Husna; Nusi, Dewanti R; Mulyaningsih, Sri; Sondakh, Levana (STIKes Hamzar, 2025)
Anemia is a condition characterized by a decrease in hemoglobin levels. One common complication during the postpartum periode is postpartum hemorrhage, which can be caused by anemia of mothers, as it can slow down wound healing, increase the risk of infection, recude brrast milk production, and cause extreme fatigue that interferes with mothers’ ability to care for newborns. Young coconut water consumption on increasing hemoglobin levels in postpartum mothers. The design used was a quasi-experiment with a pre-post test and a control group design involving a sample 0f 32 postpartum mothers divided into 16 intervention and 16 control groups. The result indicated that 10 mothers experienced an increase in hemoglobin levels after being given youngcoconut water, while six mothers experienced a decrease in hemoglobin levels. The p-value obtained was 0.045 < 0.05. Conclusion: young coconut water consumption increased hemoglobin levels in postpartum mothers at Limboto Health Center.